Ageing and Care of Older Persons in Southern Africa: Lesotho and Zimbabwe Compared - Jotham Dhemba; Bennadate Dhemba (Social Work and Society)
This article examines how two countries in Southern Africa, namely Lesotho and Zimbabwe are responding to the needs and rights of their growing ageing population. In spite of rapid population ageing and the attendant risks of abuse, neglect, poverty, ill-health and institutionalisation among others, care systems for older persons in both Lesotho and Zimbabwe are limited in scope and scale. This is mainly because of underdeveloped social protection measures and the dominance of the outdated assumption that families are obliged to look after their own older members. In spite of the pervasiveness of poverty in both countries, their public assistance schemes which are potentially the main source of financial assistance for older persons are perennially underfunded and exclusionary as they are means-tested. Older persons in both countries also experience challenges in accessing health services due to shortages of drugs, medical personnel and geriatric care facilities. However, older persons in Lesotho aged 70 years and above are relatively more financially secure as they receive universal pension of about US$ 45 monthly, unlike their Zimbabwean age mates without such a scheme. It is also important to note that the institutionalisation of older persons is shunned in both countries and it is only done as a last resort. For Lesotho and Zimbabwe to reap a"longevity dividend," it is necessary to broaden the coverage of older persons by existing social protection measures and to implement provisions of policies and legislation on the same. It is also necessary to decentralise social services for older persons to the community level.